(untitled) (Conversatoria Linguistica, 2019)
The article is devoted to the linguistic means used by country dwellers to express their thoughts on death and afterlife. The dialectal data, collected in central Poland, have been divided according to thematic groups, and within each group cognate words have been examined focusing among other on: a) the presence of Christian words common with all-Poland langage, see: soul, heaven, death; b) their considerable variantivity, see: the departed, dead, corpse; c) the expressive and stylistic tinge, see: cmentarzyk (small graveyard), trumienka (small coffin); d) the linguistic processes: assimilation, dissimilation and metathesis.